Measurement of lower limb segmental excursion using inertial sensors during single limb stance. (11th April 2018) - Kim, Kyoung Jae; Agrawal, Vibhor; Bennett, Christopher; Gaunaurd, Ignacio; Feigenbaum, Luis; Gailey, Robert
Abstract: Advances in wearable technology have afforded health scientists and clinicians the ability to quantify clinically meaningful kinematic data with performance-based outcome measures in a variety of environments. However, no method for assessing segmental excursion of the lower limb during single limb stance (SLS) with wearable technology has been described in the literature nor has its clinical meaning been explored. This study introduces a clinically friendly measure to quantify lower limb segmental excursion during SLS with inertial measurement units (IMUs) which called the region of limb stability (ROLS). The purpose of this study was to determine the concurrent validity of an IMU-based system versus an optical motion capture system and to determine the effects of knee injury on the ROLS value. Excursion areas of five healthy adults were calculated with the IMU-based system and data were compared with an optical motion capture system. There were high correlations (0.82–0.93) and no significant difference ( p > 0.05) in the tested parameters between the optical- and IMU-based systems. The IMU-based method was also implemented in five Division I athletes with knee injuries to determine changes in ROLS due to the injury. The ROLS Symmetry Index value offered a higher sensitivity and specificity to assess the presence of knee impairment than the sacral IMU. Quantified lower limb segmental excursion via IMUs can make better and more precise return-to-sport decisions that would decrease the risk of re-injury.